Manga sōdōin sugoroku (Tōkyō : Kanai Shinseidō, 1937)
The game sheet depicts well-known comic characters from Japan and United States travelling together to exotic countries and encounter various animals and people as well as with some military tanks of opponents. Descriptions are very general and don't contain proper nouns of particular places.
Title from the print.
Keywords: Sugoroku (Game); Adventure travel -- Japan -- Pictorial works; Boop, Betty (Fictitious character); Mouse, Mickey -- (Fictitious character); Board games -- Japan